Discourse On Western Development Plans In Post-Colonial British West Africa - Oluwaseun Osadola (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
This scholarly discourse seeks to provide a comprehensive analysis of the Western Development Plan that was executed in British West Africa during the post-colonial era. Academics have examined the portrayal of the British colonial government from different viewpoints and perspectives. Distinguished African academics have thoroughly examined this topic from an angle of self-interest, whereas highly regarded European scholars have analysed it from the standpoint of imperialism. The connections and affiliations between African states and their European counterparts have had negative consequences for their economic sustainability and cultural cohesion. Therefore, it is indisputable that the economies of post-colonial Africa are primarily shaped by the enduring impacts of their colonial past. The colonial economies were tightly interconnected with the economic systems of their respective metropolitan powers via a range of measures, such as currency manipulation, trade restrictions, and infrastructure expansion. This article provides a thorough review of the development plans created after the attainment of Nigeria's independence with the aim of reporting their effects on the economy and growth of West Africa.